Advisory Opinions under Protocol No. 16 to the ECHR. A Theoretical and Empirical Analysis of the Legal Nature of the ‘Questions of Principle’ - Albanesi, E. (Frontiers in Law, 2025)
One of the most significant legal arguments against the ratification of Protocol No. 16 to the European Convention on Human Rights (ECHR) is that advisory opinions issued by the European Court of Human Rights (ECtHR) would pose a threat to national sovereignty and judicial discretion. Several counterarguments have already been examined by scholars. The counterargument that will be demonstrated here is that advisory opinions cannot pose a threat to national sovereignty or judicial discretion because they are issued on ‘questions of principle’. In other words, this means that the requesting domestic highest courts or tribunals keep sufficient margin of discretion, when it comes to the concrete case brought before them. Such hypothesis will be demonstrated from a theoretical perspective, reflecting upon the legal concept of ‘principle’; and through an empirical analysis of the advisory opinions issued so far by the ECtHR. Demonstrating the hypothesis would be relevant in order to allow the States to understand that the ratification of Protocol No. 16 would not pose any threat to the discretion of domestic Courts, neither in theory nor in practice.